TOWARDS AN ANALYTICAL THEORY OF HARMONIC COUNTERPOINT (Mūzikas akadēmijas raksti, 2024)
Harmonic counterpoint is to be understood as the counterpoint made up of the melodic patterns of individual voices within chord progressions. An essential aspect of counterpoint is the hierarchy of structural levels. In particular, it is Schenkerian analysis that arranges all the structural elements of a composition into a hierarchy of structural levels. However, as an analytical theory of harmonic counterpoint, it is not quite satisfactory. In the theory proposed in this article, the harmonic counterpoint will be analysed, using the method of contrapuntal analysis based on a five-part voice-leading matrix, rather than the two-part Schenkerian Ursatz, as the high-level structure of tonal counterpoint, and exemplified by the analysis of Chopin’s Prelude in C minor (Op. 28, No. 20).